Prevalence, associations and characteristics of severe uncorrected refractive error in the Australian National Eye Health Survey. (16th October 2019) - Keel, Stuart; McGuinness, Myra B.; Foreman, Joshua; Scheetz, Jane; Taylor, Hugh R.; Dirani, Mohamed
Abstract: Importance: In Australia, nationally representative data of the burden and associations of severe uncorrected refractive error are scarce. Background: To report the prevalence and characteristics of severe uncorrected refractive error in Indigenous and non‐Indigenous Australians. Design: Population‐based cross‐sectional study. Participants: A total of 3098 non‐Indigenous Australians aged 50 to 98 and 1738 Indigenous Australians aged 40 to 92 living in 30 randomly selected Australian sites were examined. Methods: Severe uncorrected refractive error was defined as an improvement of ≥2 lines on the logMAR chart in one or both eyes in participants with a presenting visual acuity <6/12. Main Outcome Measure: Severe uncorrected refractive error Results: Prevalence of severe uncorrected refractive error was 11.0% (95% confidence interval 9.3‐13.0) in non‐Indigenous and 14.5% (12.5‐16.7) in Indigenous Australians. Eighty‐two percent of non‐Indigenous and 77% of Indigenous participants had a spherical equivalent refraction between −2.00D and +2.00D. Indigenous Australians who were older (odds ratio [OR] for 70‐79 years vs 40‐49 years = 3.59), resided in outer regional areas (OR = 1.78) and did not have an eye examination in the previous 2‐years (OR = 1.50) were associated with higher odds of severe uncorrected refractive error. Geographical remoteness (OR = .68 for inner regional), male gender (OR = 1.30), older age (OR for 70‐79 years vs 50‐59 years = 1.51) and failure to have an eye examination in the previous 2‐years (OR = 2.06) were associated with severe uncorrected refractive error among non‐Indigenous participants. Conclusions and Relevance: Increased public awareness of the importance of regular optometric examinations may be required in groups at high risk of severe uncorrected refractive error.